A host plant genome (Zizania latifolia) after a century‐long endophyte infection. (7th July 2015) - Guo, Longbiao; Qiu, Jie; Han, Zujing; Ye, Zihong; Chen, Chao; Liu, Chuanjun; Xin, Xiufang; Ye, Chu‐Yu; Wang, Ying‐Ying; Xie, Hongqing; Wang, Yu; Bao, Jiandong; et al.
Summary Despite the importance of host–microbe interactions in natural ecosystems, agriculture and medicine, the impact of long‐term (especially decades or longer) microbial colonization on the dynamics of host genomes is not well understood. The vegetable crop 'Jiaobai' with enlarged edible stems was domesticated from wild Zizania latifolia (Oryzeae) approximately 2000 years ago as a result of persistent infection by a fungal endophyte, Ustilago esculenta. Asexual propagation via infected rhizomes is the only means of Jiaobai production, and the Z. latifolia–endophyte complex has been maintained continuously for two centuries. Here, genomic analysis revealed that cultivated Z. latifolia has a significantly smaller repertoire of immune receptors compared with wild Z. latifolia. There are widespread gene losses/mutations and expression changes in the plant–pathogen interaction pathway in Jiaobai. These results show that continuous long‐standing endophyte association can have a major effect on the evolution of the structural and transcriptomic components of the host genome.